Carbon monoxide poisoning during camping in Korea. (5th December 2016) - Kim, Youn-Jung; Sohn, Chang Hwan; Oh, Bum Jin; Lim, Kyoung Soo; Kim, Won Young
Abstract: Objective : The aim of this study was to evaluate the epidemiology and characteristics of unintentional carbon monoxide (CO) poisoning during camping in Korea. Methods : We performed a retrospective observational study on patients with unintentional camping-related CO poisoning who were admitted to the emergency department (ED) from 1 January 2010 to 31 December 2014. News reports about incidents of camping-related CO poisoning were collected using news search engines. Results : A total of 72 patients (29 patients involved in 12 incidents, who were admitted to our ED, and 43 victims involved in 17 incidents reported in the media) were identified. Accidental camping-related CO poisoning occurred most frequently in May, late spring in Korea. Gas stove use and the burning of charcoal for tent heating were responsible for camping-related CO exposure. Seventeen victims (39.5%) were found dead when an ambulance arrived at the scene, in the cases reported in the media. In contrast, all the victims at our hospital were alive on hospital discharge. Twelve of the 17 incidents (70.6%) reported in the media were accidental fatalities. The majority of our patients (83.4%) were not aware of the potential danger of charcoal as a source of CO. Conclusion : Accidental camping-related CO poisoning occurred because of an ongoing lack of awareness about the potential danger of charcoal grills and stoves, and this caused prehospital mortality. Such accidents could be prevented by increasing the awareness of the potential danger of using charcoal grills and stoves during camping, as well as by establishing appropriate safety regulations.